If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 61 + -2x = 7x + 17 Reorder the terms: 61 + -2x = 17 + 7x Solving 61 + -2x = 17 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 61 + -2x + -7x = 17 + 7x + -7x Combine like terms: -2x + -7x = -9x 61 + -9x = 17 + 7x + -7x Combine like terms: 7x + -7x = 0 61 + -9x = 17 + 0 61 + -9x = 17 Add '-61' to each side of the equation. 61 + -61 + -9x = 17 + -61 Combine like terms: 61 + -61 = 0 0 + -9x = 17 + -61 -9x = 17 + -61 Combine like terms: 17 + -61 = -44 -9x = -44 Divide each side by '-9'. x = 4.888888889 Simplifying x = 4.888888889
| 8-5r+16=-21 | | 4x^2-12x=-4x^2-3x-1 | | x/3-2=6 | | -5x=+x-1 | | 3x+9=6(x-2) | | -54-10x=10x+16 | | 2(-3)-5y=13 | | 9k+ar=r-2y | | 32=-4(3p+7) | | -1=-5x | | 2(-3)5y=13 | | 3-(2x-5)=7 | | 2(5m-6)=28 | | p-3q=10 | | 3(2a+1)-4=11 | | 9v^2=-30v-25 | | 6x-5x=+1 | | 6w-14-9w=-5 | | 5-3*-1= | | 12y-3y+7=88 | | 8x^2+3x-7=0 | | 22p+11= | | 8(y+3)=2(2y+4) | | 4w^2+5=-21w | | 2(3)-5y=13 | | 7y=20 | | 3(x-2)+4x=8 | | 3x-10-5+6x=12 | | 4(7x-2)-16x= | | 7u=2u^2-4 | | z^2-13z+18=0 | | 5x(x-23)=-37 |